A Study of Inter Linkages of Stock Exchanges of Islamic Countries and US (Global Journal of Management and Business Research, 2015)
In the present era of globalization the trade is also interdependent in between the countries. The investors want to diversify the investments so that if he faces the loss from one side, he may recover it from the other side. In the case of stock exchanges, the investor wants to invest in the global stock exchange where there is no correlation among the stock exchanges. The current study attempts to study the interlinkage between the USA and Islamic countries. The study had chosen the Jakarta Stock Exchange (JKSE) from Indonesia, TASE from Israel (TA100), Kuala Lumpur Stock Exchange (KLSE) from Malaysia, Karachi Stock Exchange (KSE) from Pakistan and NYSE from USA for the purpose of the study. The closing data from 1st April 2005 to 31st Marc 2015 has been taken as the sample. For the analysis study used Auto Correlation, Unit root test, Granger Causality and Vector auto regression.
Keywords: trade; investment; interlinkage; regression